Bacteriocins Targeting Gram-Negative Phytopathogenic Bacteria: Plantibiotics of the Future - Rooney, William M.; Chai, Ray; Milner, Joel J.; Walker, Daniel (Frontiers in Microbiology, 2020)
Gram-negative phytopathogenic bacteria are a significant threat to food crops. These microbial invaders are responsible for a plethora of plant diseases and can be responsible for devastating losses in crops such as tomatoes, peppers, potatoes, olives and rice. Current disease management strategies to mitigate yield losses involve the application of chemicals which are often harmful to both human health and the environment. Bacteriocins are small proteinaceous antibiotics produced by bacteria to kill closely related bacteria and thereby establish dominance within a niche. They potentially represent a safer alternative to chemicals when used in the field. Bacteriocins typically show a high degree of selectivity towards their targets with no off-target effects. This review will outline the current state of research on bacteriocins active against Gram-negative phytopathogenic bacteria. Furthermore, we will examine the feasibility of weaponising bacteriocins for use as a treatment for bacterial plant diseases.